Development of Multiple Representation Based Physics Module to Improve Students' Conceptual Understanding and Scientific Attitude - Maisaroh; Munatayeva, Elmira; Rakhymbekova, Venera; Islami, Nur; Nasir, Muhammad (FKIP - Universitas Riau, 2025)
The module facilitates students' comprehension of physics lessons. Previous research indicates that multiple representation based physics module can improve conceptual understanding and scientific attitudes. This study aims to develop and evaluate a physics module based on multiple representation on the topic temperature and heat using the ADDIE model. The module was validated by three experts based on specific indicators and assessed for practicality by three teachers and 20 students. This study employs a quasi-experimental design with a nonequivalent control group design. Eleventh grade students were divided into an experimental class, which utilized the module, and a control class, which used conventional textbooks. Validation results indicate scores of 3.80 for content, 3.67 for pedagogy, and 3.67 for media aspects. The module's practicality was also rated highly by teachers and students, with scores of 3.76 and 3.70, respectively. The use of this module significantly improved students' conceptual understanding and scientific attitudes (Sig. < 0.05), demonstrating that the developed module is valid, practical, and effective for physics learning